Optimization of motivational variables in expressive activities in Physical Education - Sevil Serrano, J.; Abarca-Sos, A.; Julián Clemente, J. A.; Murillo Pardo, B.; García-González, L. (SPORT TK-EuroAmerican Journal of Sport Sciences, 2016)
Despite the importance of artistic expressive activities in the formation of student identity, experiences in this type of content are not always positive. This study aims to evaluate the development of a teacher intervention program to generate a motivational climate task and to check the effect of different variables integrated into the self-determination theory (Deci y Ryan, 1985). The design of the study was intra-group. 95 students (M age = 12,35; SD = 0,63) were involved during two corporal expression units of 10 sessions, respectively, in Physical Education. A series of strategies connected with TARGET areas were applied in the experimental jumping rope unit. In the control unit focused on traditional dance were applied the conventional methodology based on comprehensive learning. At the end of the two didactic units different motivational variables were measured: motivational climate (EPCM), basic psychological needs (BPNES), self-determined motivation (SIMS-14) and affective consequences (SSI-EF). The results in the experimental unit showed greater motivational task climate, satisfaction of basic psychological needs, self-determined motivation as well as enjoyment. There were significantly lower values ego climate, motivation and boredom. The importance of a teacher intervention to generate a task climate is highlighted, especially in corporal expression activities. This can result in a greater students’ motivational process, generating positive and more adaptive consequences in corporal expression content block.